Levantamento dos desastres desencadeados por eventos naturais adversos no estado do Rio Grande do Sul no período de 1980 a 2005 - Reckziegel, Bernadete Weber (2007)
The state of Rio Grande do Sul has often been scenery of the occurrence of natural disasters associate geomorphologics and atmospheric processes whose consequences are significant social and material losses. In such context, the present paper has as main purpose to accomplish the assessment of the natural disasters provoked by events of flood, torrent, riverbank erosion, gale, hailstorm, gale accompanied by hailstorm, tornado, hurricane, drought, and sliding which have occurred on the state of Rio Grande do Sul during the period comprised between the years of 1980 and 2005. Data regarding the disasters have been researched by the Zero Hora newspaper s collection and in the Official Diary of the state of Rio Grande do Sul and later presented in annual cartograms and frames shown in the Volume II of the present dissertation. The disasters verified have been separately described by event and by year of occurrence. Lately, they were analyzed in a general way, identifying the more frequent element to cause disasters as well as the monthly and seasonal arrangement of the registered events. The work is separated in seven chapters, which are presented in two volumes, treating respectively of: Introduction, which presents a brief explanation on the subject researched and the purposes of the dissertation; Literature Review, where are shown an evolution of the studies related to natural disasters, a review on some concepts applied in studies of disasters, and an explanation with respect to the statutes of Emergency Situation and State of Public Calamity; Methodological Procedures; Characterization of the Sul-riograndense geographic space; Annual description of the verified data; General analysis of the natural disasters occurred on the state between the years of 1980 and 2005 and; Final Considerations. The volume II shows the annual maps with the disasters represented by municipal districts as well as the frames listing the whole events verified along this work.